(untitled) - Hassan Bin Zubair,; Anum Saeed,; Saima Larik, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This research studies the Indian writer Rabindranath Tagore's Bangali novel Ghar Bahire which was translated by Surendranath Tagore as The Home and the World. This research examined through the perspective of modernity. It observes how the Indian people are affected through the modern way of life. Modernity affects the traditional Indian way of life. They are in a dilemma, either to follow the modern way of life or to continue their tradition and customs. It also focuses on how modernity makes man torn between his own and others.Rabindra Nath Tagore's famous novel The Home and the world has presented the issue of tension between tradition and Modernity in colonial Indian society. Because of tension, there are internal dynamics in Indian society and the Indian nation-state in general. The tension is primarily seen between the female and male characters and male-male characters. As well that represents the tradition and modernity respectively. Moreover, the industrial revolution, colonial mentality, and modern hypocrisy have a remarkable influence on the characters which further supports adding some bricks in the emergence of tension. Tagore also depicted colonial Indian life.This research highlights the tension between tradition and modernity. When modernity enters South Asian Countries there was a kind of change in the activities of Indian people. Even women also try to cross the boundary due to the impact of western education. Women started raising their voices for women's rights. Tagore presents Bimala as a radical character who tries to cross the traditional Indian role of a housewife. Due to her stupidity and submissiveness, she is unable to know the trick of Sandip who is a selfish man. Nikhil is also a modernist character. Due to his overconfidence and rationality, he died at the end of the novel.